Gender Analysis of Iddah and Ihdad as Instruments of Justice-Oriented Islamic Social Education - Hidayati, Lailatul; Habibi, Mukhlas (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This study aims to analyze the Islamic concepts of iddah (waiting period) and ihdad (mourning period) using a gender approach within the framework of Islamic social education. The central focus of the research is to explore how legal provisions related to a woman’s waiting period after divorce or the death of her husband can be interpreted more justly, reflectively, and educationally. The research subjects include Qur’anic verses and hadiths related to iddah and ihdad, as well as the works of contemporary Muslim scholars who advocate for gender justice in Islamic thought. This qualitative research employs a library research method with descriptive-critical analysis techniques, drawing on primary sources such as classical tafsir, Islamic jurisprudence (fiqh), and hadith collections, alongside contemporary academic literature and gender-focused Islamic scholarship. The findings reveal that iddah and ihdad are not merely normative legal constructs, but also contain rich educational and social values such as protection, emotional reflection, respect for marital bonds, and social responsibility toward women. The gender approach offers a progressive interpretive lens that recontextualizes these laws to promote relational justice and ethical equilibrium. This study recommends that Islamic education should incorporate gender-sensitive interpretations of fiqh in order to cultivate a more humane, contextual, and transformative understanding of Islamic law. This study offers a novel synthesis of gender-sensitive hermeneutics and Islamic social education, shedding new light on the ethical and educational dimensions of women’s post-marital rights in Islam.